The effect of physical activity on depression in university students: the mediating role of self-esteem and positive psychological capital - Wei, Xiaolong; Lai, Zhijie; Tan, Zhaowen; Ou, Ziyue; Feng, Xueyou; Xu, Guoqin; Ai, Dongsheng (Frontiers in Psychology, 2024)
This study aimed to investigate the relationship between physical exercise and depression among college students, focusing on the mediating role of self-esteem and positive psychological capital. Group psychological measurements were conducted on 579 students using various scales, including the Physical Activity Rating Scal (PARS-3), Self-esteem Scale (SES), Positive Psychological Capital Questionnaire (PPQ), and Self-rating Depression Scale (SDS). The data were analyzed using SPSS 26.0 and bootstrap methods to test and analyze the effects. The results indicated a negative correlation between physical exercise and depressive mood, with physical exercise significantly predicting college students' depressive mood. Additionally, physical exercise was found to positively predict self-esteem and positive psychological capital, both of which are negatively predictive of depressive mood. Self-esteem and positive psychological capital were identified as significant mediators between physical exercise and depressive mood, with three mediating paths: physical exercise, self-esteem, and depressed mood (Path 1). Physical exercise, positive psychological capital, and depression emotion (Path 2). Physical exercise, self-esteem, positive psychological capital, depressed mood (Path 3). In conclusion, physical exercise negatively predicts college students' depressive mood and has a mediating effect through self-esteem and positive psychological capital, with a chain-like impact on college students' depression.